A Short Bout of Exercise With and Without an Immersive Virtual Reality Game Can Reduce Stress and Anxiety in Adolescents: A Pilot Randomized Controlled Trial - Shaw, Alexa J.; Lubetzky, Anat V. (Frontiers in Virtual Reality, 2021)
Anxiety and stress are prominent issues for the adolescent population. Physical activity is known to reduce symptoms of anxiety and stress; however, many adolescents lack the time or motivation to exercise regularly, particularly during stressful exam weeks. Virtual Reality (VR) has the potential to make exercise more enjoyable and more engaging than exercise alone. We aimed to investigate the immediate effect of a 10-minute dodgeball exercise session, with and without a VR headset, on self-reported stress, anxiety and cognitive performance in adolescents during times known to induce stress in high school, such as exam weeks. Participants were randomly assigned to a VR group (n=16) where participants were immersed in a virtual dodgeball environment (exergame), or a dodgeball group (n=14) which played a simple game of one-on-one dodgeball. Executive function was measured using the Trail Making Test (TMT) Parts A & B. Anxiety was self-reported on the Pediatric Anxiety Short Form 8a (PASF). Stress was self-reported on the Psychological Stress Experiences-Short Form 8a (PSES). Both groups significantly improved their TMT A & B performance and reduced stress and anxiety scores with effect size ranging from 0.59 to 1.2 (main effect of time P<0.001 for all outcomes). There were no significant differences between groups and no time by group interaction for any outcome. A short bout of exercise, with or without VR, during stressful high school exam weeks was shown to be effective for immediate reduction of stress and anxiety and enhancement of cognitive function in a small sample of high school students. High schools looking to apply interventions to help their students manage anxiety and stress should consider encouraging them to take a “time-out” to exercise and play. The cost-effectiveness of exergames inside the school settings and implications for academic success should be investigated in future research.